The Life-Cycle of the HIV-1 Gag–RNA Complex - Elodie Mailler; Serena Bernacchi; Roland Marquet; Jean-Christophe Paillart; Valérie Vivet-Boudou; Redmond P. Smyth (Viruses, 2016)
Human immunodeficiency virus type 1 (HIV-1) replication is a highly regulated process requiring the recruitment of viral and cellular components to the plasma membrane for assembly into infectious particles. This review highlights the recent process of understanding the selection of the genomic RNA (gRNA) by the viral Pr55Gag precursor polyprotein, and the processes leading to its incorporation into viral particles.